Caffeine regulates GABA transport via A1R blockade and cAMP signaling. (December 2019) - Borges-Martins, Vladimir Pedro Peralva; Ferreira, Danielle Dias Pinto; Souto, Arthur Cardoso; Oliveira Neto, Jessika Geisebel; Pereira-Figueiredo, Danniel; da Costa Calaza, Karin; de Jesus Oliveira, Karen; Manhães, Alex Christian; de Melo Reis, Ricardo Augusto; Kubrusly, Regina Célia Cussa
Abstract: Caffeine is the most consumed psychostimulant drug in the world, acting as a non-selective antagonist of adenosine receptors A1 R and A2A R, which are widely expressed in retinal layers. We have previously shown that caffeine, when administered acutely, acts on A1 R to potentiate the NMDA receptor-induced GABA release. Now we asked if long-term caffeine exposure also modifies GABA uptake in the avian retina and which mechanisms are involved in this process. Chicken embryos aged E11 were injected with a single dose of caffeine (30 mg/kg) in the air chamber. Retinas were dissected on E15 for ex vivo neurochemical assays. Our results showed that [ 3 H]-GABA uptake was dependent on Na + and blocked at 4 °C or by NO-711 and caffeine. This decrease was observed after 60 min of [ 3 H]-GABA uptake assay at E15, which is accompanied by an increase in [ 3 H]-GABA release. Caffeine increased the protein levels of A1 R without altering ADORA1 mRNA and was devoid of effects on A2A R density or ADORA2A mRNA levels. The decrease of GABA uptake promoted by caffeine was reverted by A1 R activation with N6-cyclohexyl adenosine (CHA) but not by A2A R activation with CGS 21680. Caffeine exposure increased cAMP levels and GAT-1 protein levels, which was evenly expressed between E11-E15. As expected, we observed an increase of GABA containing amacrine cells and processes in the IPL, also, cAMP pathway blockage by H-89 decreased caffeine mediated [ 3 H]-GABA uptake. Our data support the idea that chronic injection of caffeine alters GABA transport via A1 R during retinal development and that the cAMP/PKA pathway plays an important role in the regulation of GAT-1 function. Highlights: Caffeine reduces [ 3 H]-GABA uptake via GAT-1 and increases [ 3 H]-GABA release. Caffeine increases A1 R protein levels. Caffeine effects depend on A1 R function. GAT-1 function is dependent on cAMP levels and PKA activity.